PENGARUH KUALITAS SISTEM, KUALITAS INFORMASI, KEMUDAHAN PENGGUNAAN E-FILING TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - I Wayan Kartana; Ni Nengah Seri Ekayani; I Gede Aryawan; Ida Ayu Sri Meitri (JURNAL AKUNTANSI, 2023)
E-Filing is a system that regulates how to submit or report taxes and submit notifications for online renewal of Annual SPT, where all SPT payment activities can be done without having to meet face to face and can be done anywhere and anytime. The Directorate General of Taxes has implemented this e-filing system in 2007. This research is trying to assess the system information success by collaborating system information success models of DeLone and McLean (2003) which has been modified by Wang and Liao (2008) which only takes two variables, which is System Quality, Information Quality. Technology Acceptance Model Davis (1989) which only takes one variable, namely Ease of Use of E-Filing and Taxpayer Awareness as moderating variables. This research is using primary data types. The method of determining the sample using sampling incidental technique, amounting to 200 respondents. Data is obtained by using questionnaire which was filled directly by the respondent as well as through an online google form. Hypothesis testing is carried out using a variant-based Structural Equation Model (SEM) or what is commonly called Partial Least Square. The result is that System Quality has a significant positive effect on Individual Taxpayer Compliance. Information Quality has no effect on Individual Taxpayer Compliance. Ease of Use of E-Filing has no effect on Individual Taxpayer Compliance. Furthermore, Taxpayer Awareness does not moderate the influence of System Quality on Individual Taxpayer Compliance, Taxpayer Awareness does not moderate the effect of Information Quality on Individual Taxpayer Compliance, Taxpayer Awareness does not moderate the effect between Ease of Use of E-Filing on Taxpayer Compliance Private Person.